PENYEBAB KECELAKAAN KERJA, AKIBAT KECELAKAAN KERJA, PENCEGAHAN DAN PENANGGULANGAN KECELAKAAN KERJA (Literatur Review) - Anjas Thoriqi; Yulia Safitri; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2023)
Work accident (work accident) is an unwanted incident or event that is detrimental to humans, damage to property or loss to the process. The occurrence of work accidents is caused by two main factors, namely physical factors and human factors. In their daily work, health workers are always faced with certain hazards, for example infectious hazards, toxic reagents, electrical equipment and medical equipment. As for how to control the work environment to minimize accidents for workers, namely by technical control, administrative control and using Personal Protective Equipment (PPE).